Hybrid nanostructure of SiO2@Si with Au-nanoparticles for surface enhanced Raman spectroscopy. Issue 28 (10th July 2019) - Yang, Huan; Li, Ben Q.; Jiang, Xinbing; Shao, Jinyou
Abstract : Hybrid resonance enhanced local electric field for Raman sensing. Abstract : In this study, a structure of large-area orderly-arranged SiO2 @Si core–shell nanoparticles decorated with Au nanoparticles was fabricated for surface-enhanced Raman spectroscopy (SERS). This hybrid structure features light confinement in the Si shells and a uniform distribution of localized electric hot spots. FDTD simulations were carried out to examine the near-field enhancement response of this structure. Results indicate that the strongly enhanced local electric field is attributed to the WGM–LSPR coupling, that is, the coupling of the whispering gallery mode (WGM) of Si nanoshells with the localized surface plasmon resonance (LSPR) of Au nanoparticles. The excitation of WGM comes primarily from the magnetic response of the Si shell with a minor modification by its electric response. The WGM–LSPR coupling of the structure is tunable through the change of geometric parameters of SiO2 @Si particles. Raman scattering measurements were conducted on the samples fabricated, which agree well with the simulated results. The measured data gave a SERS G factor of ∼2 × 10 8 and showed highly sensitive and reproducible SERS signals of R6G with a high spatial uniformity on a 2 × 2 cm 2 substrate consisting of an array of SiO2 @Si ( D = ∼220 nm/290 nm) particles whose outer surfaces were scattered with d = ∼20 nm Au particles.